PERBANDINGAN AKTIVITAS ANTIBAKTERI EKSTRAK KULIT BATANG SUNGKAI DAN KULIT BATANG TANJUNG TERHADAP Staphylococcus aureus IN VITRO - Nosi Kusuma Winarno Putri; Noor Muthmainah; Agung Biworo (Homeostasis, 2022)
Sungkai and tanjung plants are medicinal plants which used to cure various diseases, including the following diseases that are caused by Staphylococcus aureus. Sungkai bark contains alkaloids, phenols and terpenoids, tanjung bark contains alkaloids, tannins, flavonoid, and saponins which have antibacterial traits. The aim of the study is to compare the antibacterial activity of sungkai and tanjung bark extracts against S. aureus in vitro. True experimental with post-test only, also using control group design is the chosen research method used upon this research. The 8 treatments of sungkai bark extract and tanjung bark extract with concentration of 25%, 50%, 75%, and 100%, clindamycin 2 µg as control positive, and control negative. The method used for extraction was maceration with 70% ethanol as solvents. The parameter measured was the diameter of the resistance. The average results of inhibition zones with a consensus of 25%, 50%, 75%, 100% sungkai bark extract were 8.27 mm, 10.42 mm, 12.08 mm, 15.38 mm, and the tanjung bark were 13.05 mm,. 16.42mm, 19.57mm, 21.20mm. Data analysis used one-way ANOVA, post-hoc LSD and Independent T with 95% accuracy. The study concludes that there were differences that is stastistically signifficant of antibacterial activity between sungkai and tanjung bark extracts against S. aureus in vitro..